Implementing a Senior Statistics Practicum: Lessons and Feedback from Multiple Offerings. Issue 2 (4th May 2022) - Paloian, Sierra; Doehler, Kirsten; Lahetta, Alexandra
Abstract: A Statistics Practicum course is offered as another option besides an internship or research experience for students to fulfill a required statistics major capstone experience. This article discusses the first and fourth offering of this practicum course, which provides a unique perspective on the initial implementation of the course and its development over time. The course offers students opportunities to carry out statistical consulting projects with external clients. Students were given multiple reflection assignments throughout the course. Challenges of the projects were discussed in the reflections, which included issues of data cleaning and analysis. Students also responded to both Likert-scale and open-ended questions on an end of semester survey. These responses provided information on sentiment regarding the consulting projects and perceived usefulness of various components of the Statistics Practicum course. Both student reflection assignments and survey responses were analyzed in this study. Explanations of the thought processes that went into setting up and running the course are included. Advice and suggestions for course improvements and successful administration are also presented.